JOURNAL OF GOVERNMENT & POLITICS : The Empowerment of Marginalized Community (Street Vendors) for Developing Creative Economy in Payakumbuh City West Sumatra - Syamsir (FISIPOL UMY, 2016)
This study generally aimed to find a model for empowerment of the marginalized community of street vendors for developing creative economy in Payakumbuh City, West Sumatra